Torsional vibration of suspension bridge with a variable cross section - Tinh, Nguyen Van (Vietnam Journal of Mechanics, 1981)
The transfer matrix method to torsion’ al vibrations of a suspension bridge with variable cross sections is reported. The method described above is particularly suitable for implementing an efficient computer program. A numerical example is also givens.